Better banks for Eastern Europe - Holger Schmieding; Claudia Buch (Institut für Weltwirtschaft (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1992)
Grossly inefficient banking systems are one of the major impediments to a rapid and sustained upswing in Europe's emerging market economies (EMEs for short). Although the transition from plan to market necessitates a large-scale re-allocation of domestic capital and easy access to foreign capital, the EMEs have adopted slow and inefficient approaches to the transformation of their banking systems. The EMEs can create optimal conditions for financial intermediation and a substantial import of capital and skills if they immediately import an efficient banking system and enter into an East-West Banking Union with the EC. A Banking Union goes far beyond the adoption of some relevant EC regulations for local banks; it gives all financial intermediaries licensed in one EC country free access to the EMEs subject to the same rules that apply in the EC internal market. At present, non-performing loans still tie state banks to insolvent state enterprises; the precarious portfolio positions of domestic banks serve as a convenient excuse for not allowing efficient and experienced Western banks to enter the market in the EMEs. To resolve the portfolio problem at one stroke, all loans that state banks had granted to state firms prior to a certain date should be written off; tight ceilings on the amount of new credits each state firm can receive from state banks would prevent a recurrence of the problem. The ceilings should not apply to private banks, which are controlled by self-interested owners. State banks should be recapitalized using government bonds that are indexed to inflation. Since a programme of debt write-off and recapitalization raises the value of state firms and state banks and thus the potential proceeds of privatization, it need not constitute a drain on the state budget. A clean sweep, which eases the privatization of firms and banks, is preferable to a time-consuming and arbitrary case-by-case approach. Even if it is no longer politically possible to fully discard the present gradualist policies, the EMEs should at least upgrade their piecemeal debt-reduction and recapitalization programmes. Thereafter, the residual portfolio problems should no longer pose an obstacle to immediate and free market access for foreign banks within an East-West Banking Union.
Keywords: 330; Finanzsektor; Systemtransformation; Kreditpolitik; Bankenpolitik; Fremdkapital; Schulden; Osteuropa